Rancangan VFR Corridor Majalengka Control Zone di Perum LPPNPI Unit Pelayanan Kertajati - Ryan Hasibuan; Lina Rosmayanti; Agus Setiawan (Politeknik Penerbangan Indonesia Curug, 2021)
This study aims to design VFR Corridor connecting Cakrabhuwana Airport in Cirebon with Tunggul Wulung Cilacap Airport and Cijulang Nusawairu Airport.The research method used is level one research and development with a qualitative approach and descriptive exposure. Data collection techniques in the form of interviews, literature studies, and documentation studies. Meanwhile, data processing techniques use data reduction, data presentation, and verification. Based on the data collected, it is known that the flights from Cirebon to Cilacap and Nusawiru or vice versa do not have a clear VFR Corridor to connect the three airports, while the number of traffic overflying that makes Cross Country flights to Tunggul Wulung Cilacap and Cijulang Nusawiru airports is quite large.